Cross-Cultural Indonesia-Malaysia for Strengthening Learning Products to Achieve Sustainable Goals - Firmansyah Firmansyah; Asnarni Lubis; Noorjima Abdul Wahab; Ayu Utami Br. Simbolon (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity was carried out based on an international collaboration between Indonesia and Malaysia. Indonesia was represented by Universitas Muslim Nusantara Al-Washliyah (UMN Al-Washliyah), while Malaysia was represented by Universiti Sultan Zainal Abidin (UniSZA). The main focus of the program was cultural exchange as a unique foundation for creating Project-Based Learning approaches. The implementation method involved a Knowledge Transfer Programme, with UniSZA students as the primary partners. The results reveal that integrating Malay culture from both Indonesia and Malaysia strengthens cross-national educational values and significantly contributes to achieving Sustainable Development Goals (SDG) point 4, which emphasizes quality education. The empowerment of cultural identity within the educational context serves as a strategic instrument to enhance students' understanding, tolerance, and global competence.